miR-215-5p regulates osteoporosis development and osteogenic differentiation by targeting XIAP - Zilong Yin; Jian Shen; Qiang Wang; Liangyuan Wen; Wenjing Qu; Yaonan Zhang (BMC Musculoskeletal Disorders, 2022)
Abstract Background Osteoporosis (OP) is a metabolic disease that involves microstructure destruction and fracture damage. The present study probed into the significance of miR-215-5p in OP progression. Methods Serum samples were collected from surgical patients and healthy controls. qRT-PCR analysis was utilized to determine the miR-215-5p level in clinical samples and human bone mesenchymal stem cells (hBMSCs) induced by β-glycerol phosphate. A dual luciferase reporter assay was exploited to examine the targeted relationship between miR-215-5p and XIAP. The mineralization and calcium deposition of hBMSCs were assessed by detection of ALP activity, Alizarin red staining, and osteoblast marker expression. Protein expression was determined by western blot analysis. Results MiR-215-5p was significantly reduced in patients with OP and increased in hBMSCs treated with β-glycerophosphate. Enhanced miR-215-5p level triggered augment in osteoblast markers (Alkaline phosphatase/ ALP, Osteocalcin/ OCN, and Runt-Related Transcription Factor 2/ Runx2), which was accompanied by the increase of ALP activity in hBMSCs and accumulation of Calcium. Functional experiments show that XIAP was a target of miR-215-5p and negatively modulated by miR-215-5p. XIAP expression levels were increased in OP samples, and decreased XIAP in β-glycerophosphate-treated hBMSCs inhibited its’ osteogenic differentiation. Functional loss and acquisition experiments depicted that miR-215-5p promoted the differentiation of hBMSCs by inhibiting the XIAP level, playing a protective role in the pathogenesis of OP. Conclusions β-glycerophosphate promoted the osteogenic differentiation of hBMSCs, increased miR-215-5p level, and decreased XIAP. miR-215-5p stimulated osteogenic differentiation of hBMSCs by targeting XIAP, shedding new insights for the detection and therapy of OP.